DEVELOPMENT OF AN EVALUATION METHOD FOR RIVER ENVIRONMENT - H. Araki; K. Koga; Y. Nishi; Y. Kajiya; S. Imae; S. Kimura; K. Hirano; M. Sakanashi; S. Toyosaki; H. Fukuyama (Lowland Technology International, 1999)
Assessment in planning and designing process is necessary especially for nature-oriented river. The main purpose of this study is to develop an assessment method for river environment. At a workshop composed of experts on river environment, a viewpoint to identify characteristics of watershed and/or river environment was added to viewpoints of the River Council in Japan. Furthermore, the new concept of "intermediate nature" is proposed to develop a goal-oriented assessment method. In this study, the prototype of a new assessment method "EMOREK" is proposed, somewhat similar to the AMOEBA method developed in the Netherlands. A case study on the T-river in Japan was carried out to realize the capability of the assessment method through problem analysis on the river environment.